PENGARUH KUALITAS SUMBER DAYA MANUSIA PENGELOLA TERHADAP KINERJA KOPERASI DI KECAMATAN TAPUNG HILIR KABUPATEN KAMPAR - Muhammad Abror Isma; Almasdi Syahza; Hendripides ' (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstract: This study aims to determine how much influence the quality of human resource managers on the performance of cooperatives in the District Tapung Hilir, Kampar. The population in this study are all members of the Cooperative KUD totaling 3,186 members of village cooperatives. and using proportional random sampling technique in can be a total sample of 97 members of the village unit cooperatives. Data were collected using a questionnaire or questionnaires and documentation. Data were analyzed using simple regression analysis and F test with significance level of 0.05%. The research showed that the quality of human resources business simultaneously positive and significant impact on Cooperative Performance. It is based on the analysis results, which show the calculation results F count (10.606)> F table (7.709) What this means is that the SDM manager of a significant effect on the growth of business turnover. F arithmetic (0.322) <F table (7.709) What this means is that the SDM manager has no significant effect on the development of members. and F arithmetic (0.182) <F table (7.709) What this means is that the SDM manager no significant effect on the development of SHU. and the amount of contributions or donations to the quality of human resources business performance with a great show of determination of Influence business positive effect on the growth of business turnover amounted to 72.6%, while 27.4% are influenced by other factors such as the number of members, SHU, and participation member. Effect of SDM Managers will not affect the development of members is 7.5%, while 92.5% are influenced by other factors and the influence of SDM manager is not berpngaruh to the development of SHU is 4.3%, while 95.7% is influenced by factors other Factors.Key Words: Quality Of Human Resources Management, Performance Cooperation